COVID‐19 and cardiovascular problems in elderly patients: Food for thought. Issue 2 (28th February 2021) - Costa, Raffaele; Castagna, Alberto; Ruotolo, Giovanni
Abstract: The global number of COVID‐19 infections, as of December 23, 2020, stood at approximately 79 million, with over 1.7 million deaths. The development of vascular inflammation may also contribute to a hypercoagulable state and endothelial dysfunction in such patients. It is known that multi‐organ damage is more likely in patients with sepsis if they develop coagulopathy and that inhibition of thrombin synthesis can have a positive impact in reducing mortality. In this review, we will focus on the protection of the most fragile groups of the population, such as the elderly. This segment of the population will be a key issue and probably of primary interest to all. Biomarkers appear to be extremely useful as an indicator of what is happening from a pathophysiological point of view in the heart, allowing us to better stratify the prognosis of our patients affected by COVID‐19, especially in the most severe cases and those with comorbidities. Abstract : Initially, COVID‐19 disease was identified as a disease involving the respiratory tract, with the possibility of progressing to severe interstitial pneumonia and Acute Respiratory Distress Syndrome; Ever increasing data highlight the possibility that in addition to the lungs, the heart is also a possible target of the coronavirus and cardiovascular diseases seem to represent a multiplier of the risk of death in case of infection with Covid‐19.